PENGEMBANGAN MEDIA ANIMASI DENGAN APLIKASI MAKROMEDIA FLASH PADA MATERI LISTRIK STATIS - Bq Azmi Syukroyanti; Wirawan Putrayadi (Universitas Pendidikan Mandalika, 2017)
The development of learning media is very important to support teaching and learning in the classroom because abstract concepts in physics are difficult to understand. This study aims to Develop Animation Media using Macromedia Flash Application On Static Electric Material. This research uses the development of ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collected by Questionnaire. Questionnaire is used to measure program indicators relating to the content of learning media, program display, and program technical quality. Questionnaire uses a four-point response from Likert scale, where the response alternative is excellent (4 points), good (3 point), less good (2 point) and bad (1 point)